If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-7(x-(-11))=-2
We move all terms to the left:
-7(x-(-11))-(-2)=0
We add all the numbers together, and all the variables
-7(x-(-11))+2=0
We move all terms containing x to the left, all other terms to the right
-7(x-(-11))=-2
| 8(5x+7)=24 | | 4(8x-10)=2(20x-16) | | 3x^2+12x=K | | y/4+6=-10 | | 3x-13.5=7.5x | | 8(x+1)=1×10 | | 5^2+40n=5n | | 2/3x-13=32 | | 2/3x-13=16 | | 35-45=x/x | | (2x-1)/2=(2x+1)/3 | | (x+100/x^2)=0 | | 10(-3+8v)=30 | | x/x=35 | | x+15=1/2(9x-12) | | m-2/5=m+8/10 | | 3=-9(x-6) | | x+3x+2=15 | | 2k+3/k=2/3 | | x/2=35/2 | | 5+(-12)=d | | 7(x+4)=2x+20 | | 5y+37=-8 | | x-0.25x=28.80 | | 180=(7x)+(3x)+(2x) | | 4.666667+g=9 | | 13/5/x=13/4 | | 7x-3=-22 | | (10x+10)-5=15 | | v=-10=-9 | | h+4.78=8.02 | | -2(7X-7)+3(5x-1)-8=2-8 |